A novel approach to the treatment of a direct carotid–cavernous fistula in a patient with Ehlers–Danlos syndrome type IV. (28th November 2014) - Nakagawa, Ichiro; Park, Hun Soo; Wada, Takeshi; Takayama, Katsutoshi; Nakagawa, Hiroyuki; Kichikawa, Kimihiko; Nakase, Hiroyuki
Abstract : We report a case of a direct carotid–cavernous fistula (CCF) in a patient with Ehlers–Danlos syndrome type IV who presented with progressive chemosis and diplopia. To prevent potential lethal arterial wall injury due to the fragility of the arterial vessel wall, the ipsilateral carotid artery and internal jugular vein were surgically exposed for direct insertion of endovascular sheaths, and transvenous embolization was performed using triple microcatheters with detachable coils. The clinical course was uneventful, and chemosis and diplopia subsequently resolved. By the 6 month follow-up, MRI revealed no recurrence of the CCF. These techniques offer a unique access alternative for endovascular treatment, thereby reducing the risks associated with arterial dissection that often accompanies transfemoral access in this particular condition.